Epidemiological Situation on Tick-Borne Borreliosis in the Russian Federation in 2021 and Forecast for 2022 - S. A. Rudakova; O. E. Teslova; N. E. Mutalinova; N. A. Pen’evskaya; N. V. Rudakov; D. A. Savel’ev; Yu. F. Kuz’menko (Проблемы особо опасных инфекций, 2022)
3875 cases of tick-borne borreliosis (TBB) (2.65 per 100000 of population) were recorded in Russia in 2021. Compared to 2020, 61 out of 78 constituent entities experienced a decrease in the incidence rate in 2021. Over the past year, the largest number of cases was registered in the Central Federal District (CFD) – 1797 cases, which is 46.4 % of cases in Russia. Second in the rank by the number of cases of TBB comes the Siberian FD (SFD) – 616 cases (15.9 %), followed by Ural FD – 445 cases (11.5 %), the North-Western FD – 418 (10.8 %), and the Volga FD – 388 (10 %). 134 (3.5 %) and 60 (1.5 % of the total number of cases of TBB) cases were registered in the Far Eastern and Southern Federal Districts, respectively. The last place is occupied by the North Caucasus Federal District (NCFD), where 17 cases were registered, the share of which in the total structure of cases in Russia is 0.4 %. When assessing the long-term dynamics of TBB incidence, a significant trend towards a decrease in the intensity of the epidemic process has been revealed for the North-Western FD, UFD and VFD, as opposed to the CFD and Southern FD, where a significant upward trend was noted. For the Russian Federation on the whole, the Siberian FD, FEFD and NCFD the variation in the incidence rates within the confidence intervals of the long-term annual average values is most likely to be observed in the near future.